A formal approach to argumentation in group decision scenarios - Neves, José (2006)
Time and space consuming are disadvantages in group meetings but are easily faced in computer systems. Agent based group decision support systems reduce the loss usually associated to group work, turning more relevant the benefits that emerge from group meetings. Better decisions are taken after negotiation through choice and convincement. In this paper, a formal logic programming based system is proposed to represent agent knowledge and reasoning in order to be used in argumentation for decision group taking, supporting meetings where agents participate and communicate.